Loyalty programmes and their specifics in the Chinese hospitality industry: Qualitative study - Katarína Gubíniová; Thorsten Robert Moller; Silvia Trel'ová; Malgorzata Agnieszka Jarossová (Administrative Sciences, 2023)
Instead of aiming to achieve as many members as possible, it is important to focus on retaining customers, which is achieved with the support of loyalty programmes. As the tourism and hospital industries have become the fastest growing sectors in the world, hotels have realised the potential to focus on their loyal customers. A qualitative approach was adopted to explore the attractiveness of loyalty programmes to Chinese consumers and the challenges of such programmes in the hospitality industry. The aim of this paper is to identify which aspects of a loyalty programme in the hospitality industry are perceived as attractive to Chinese customers. This qualitative research highlights the perspective of industry leaders such as general managers and executives working in the club lounges of five-star hotels in Suzhou as well as loyalty programme consultants with a focus on China. The qualitative research findings are aimed at supporting hotels in China and loyalty programmes with a focus on Chinese consumers in the hospitality industry in order to receive more knowledge and to explore new strategies on how to retain and satisfy Chinese programme members.
Keywords: 350; benefits; customer; hospitality industry; loyalty; loyalty programme